The lonely crowd ; a study of the changing American character - Riesman, David; Glazer, Nathan; Denney, Reuel (New Haven : Yale University Press, 1989)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: etnologie; Verenigde Staten van Amerika